2016
DOI: 10.1111/btp.12290
|View full text |Cite
|
Sign up to set email alerts
|

Generalist Species Have a Central Role In a Highly Diverse Plant–Frugivore Network

Abstract: Analysis of plant-frugivore interactions provides a quantitative framework for integrating community structure and ecosystem function in terms of how the roles and attributes of individual species contribute to network structure and resilience. In this study, we used centrality metrics to rank and detect the most important species in a mutualistic network of fruit-eating birds and plants in a cloud forest in the Colombian Andes. We identified a central core of ten bird and seven plant species in a network of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
63
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 51 publications
9
63
1
6
Order By: Relevance
“…, Palacio et al . ). In this sense, the fact that only one (species strength) of the five metrics considered showed significant correlation between plant‐ and animal‐centered approaches could be concerning.…”
Section: Discussionmentioning
confidence: 97%
“…, Palacio et al . ). In this sense, the fact that only one (species strength) of the five metrics considered showed significant correlation between plant‐ and animal‐centered approaches could be concerning.…”
Section: Discussionmentioning
confidence: 97%
“…However, we found that while disperser diversity is always intrinsically important for seed dispersal function, it became increasingly important when frugivore abundance declined. Together, these results suggest that while a few disturbance‐tolerant generalist dispersers can, to some extent, maintain the seed dispersal service for most fleshy‐fruited species (see Palacio, Valderrama‐Ardila & Kattan ), such compensation is no longer effective when defaunation simultaneously reduces the richness of the vertebrate community and their overall abundance. Additionally, we show that the extinction order of disperser species can have a critical effect on the degradation rate of community‐level dispersal services.…”
Section: Discussionmentioning
confidence: 99%
“…While specialized frugivores are known to play a key role in plant‐disperser networks (Mello et al, ; Sebastián‐González, ), the role of large frugivores in dispersal in wider plant‐dispersal networks is still debated (Palacio, Valderrama‐Ardila, & Kattan, ; Sebastián‐González, ). The observed network was significantly less nested than null networks, contrary to the general trend (García, ).…”
Section: Discussionmentioning
confidence: 99%